2017
DOI: 10.1111/aos.13568
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of different regimens for primary open‐angle glaucoma or ocular hypertension: a systematic review and network meta‐analysis

Abstract: PurposeTo assess the efficacy and safety of different regimens, including monotherapy and double therapy, for primary open‐angle glaucoma (POAG) or ocular hypertension.MethodsWe searched PubMed, EMBASE and clinicaltrials.gov for studies that fit our inclusion criteria in this network meta‐analysis. Randomized controlled trials that report data on efficacy and safety of medications for POAG or ocular hypertension are included. Data on intra‐ocular pressure (IOP) lowering effect and incidence of adverse events i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
55
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 36 publications
1
55
0
2
Order By: Relevance
“…PGA is the most widely used first-line therapeutic medication for POAG due to its highest effectiveness in decreasing IOP [19] and reducing circadian IOP fluctuations, as well as its convenient dosing and tolerable side effects [20]. However, PGA was found to have some other effects, such as decreasing the thickness of central cornea.…”
Section: Discussionmentioning
confidence: 99%
“…PGA is the most widely used first-line therapeutic medication for POAG due to its highest effectiveness in decreasing IOP [19] and reducing circadian IOP fluctuations, as well as its convenient dosing and tolerable side effects [20]. However, PGA was found to have some other effects, such as decreasing the thickness of central cornea.…”
Section: Discussionmentioning
confidence: 99%
“…In the subgroup analysis of the current study, no significant difference is found about the rate of dementia in different subtypes of glaucoma compared to propensity score-matching subjects without glaucoma. The mechanisms of the three subtypes of glaucoma included in the current study are different; the ACG is caused by the acute elevation of intraocular pressure, while the OAG and the NTG are resulted from long-term ocular hypertensive status and possible low-perfusion condition [28,33,34]. That the incidence of dementia did not elevate in all subtypes of glaucoma may further indicate the different pathophysiologies of neurological degradation between the brain and retina, which is supported by the findings of the current study.…”
Section: Discussionmentioning
confidence: 99%
“…PGA is the most widely used rst-line therapeutic medication for POAG due to its highest effectiveness in decreasing IOP [19] and reducing circadian IOP uctuations, as well as its convenient dosing and tolerable side effects [20]. However, PGA was found to have some other effects, such as decreasing the thickness of central cornea.…”
Section: Discussionmentioning
confidence: 99%